Features of short-term variability of arterial pressure with different types of circadian rhythm in patients with hypertension disease who have suffered myocardial infarction - Kolesnyk , Tetyana; Fursa , Oleksandra (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2023)
Abstract. Blood pressure variability is an important prognostic parameter and is an independent predictor of cardiovascular disease and mortality. Aim. To assess short-term blood pressure variability with regard to the type of diurnal blood pressure profile in hypertensive patients with myocardial infarction. Materials and methods. 78 hypertensive men who had a myocardial infarction were examined. The average age was 58.0 (54.0; 67.0) years, the experience of hypertension was 9.0 (5.0; 18.0) years, the period after the myocardial infarction was 24.5 (12.0; 84,0) months. All patients underwent daily monitoring of blood pressure with the study of average day and night pressure levels, the degree of nocturnal decrease in blood pressure, blood pressure variability with STD calculation, pure and new variability indices. The results. Increased BP variability during the day and at night was registered with all types of circadian systolic BP rhythm. The highest values of systolic BP variability (STD) during the day and at night were in patients with a night-picker circadian profile. Achieving the target level of systolic BP as a whole in the group was observed in 34.6 % of patients during the day and 42.3 % at night. Patients with an over-dipper circadian blood pressure profile, despite having the highest percentage of target blood pressure achievement, had the highest values of variability characteristics calculated by STD, pure and new indices per day (p < 0.05). Conclusions. Increased blood pressure variability and pressure level at night are important criteria for assessing the prognosis of hypertensive patients after myocardial infarction. Daily monitoring of blood pressure provides a unique opportunity to objectify these prognostic parameters at different times of the day, which, together with the assessment of reaching the target level of blood pressure, is necessary to control the effectiveness of treatment.